CD209/CD14+ Dendritic Cells Characterization in Rheumatoid and Psoriatic Arthritis Patients: Activation, Synovial Infiltration, and Therapeutic Targeting - Marzaioli, Viviana; Canavan, Mary; Floudas, Achilleas; Flynn, Keelin; Mullan, Ronan; Veale, Douglas J.; Fearon, Ursula (Frontiers in Immunology, 2022)
Dendritic cells (DC) have a key role in the initiation and progression of inflammatory arthritis (IA). In this study, we identified a DC population that derive from monocytes, characterized as CD209/CD14+DC, expressing classical DC markers (HLADR, CD11c) and the Mo-DC marker (CD209), while also retaining the monocytic marker CD14. This CD209/CD14+ DC population is present in the circulation of HC, with increased frequency in Rheumatoid Arthritis (RA) and Psoriatic arthritic (PsA) patients. We demonstrate, for the first time, that circulatory IA CD209/CD14+ DC express more cytokines (IL1β/IL6/IL12/TNFα) and display a unique chemokine receptor expression and co-expression profiles compared to HC. We demonstrated that CD209/CD14+ DC are enriched in the inflamed joint where they display a unique inflammatory and maturation phenotype, with increased CD40 and CD80 and co-expression of specific chemokine receptors, displaying unique patterns between PsA and RA. We developed a new protocol of magnetic isolation and expansion for CD209+ DC from blood and identified transcriptional differences involved in endocytosis/antigen presentation between RA and PsA CD209+ DC. In addition, we observed that culture of healthy CD209+ DC with IA synovial fluid (SF), but not Osteoarthritis (OA) SF, was sufficient to induce the development of CD209/CD14+ DC, leading to a poly-mature DC phenotype. In addition, differential effects were observed in terms of chemokine receptor and chemokine expression, with healthy CD209+ DC displaying increased expression/co-expression of CCR6, CCR7, CXCR3, CXCR4 and CXCR5 when cultured with RA SF, while an increase in the chemokines CCR3, CXCL10 and CXCL11 was observed when cultured with PsA SF. This effect may be mediated in part by the observed differential increase in chemokines expressed in RA vs PsA SF. Finally, we observed that the JAK/STAT pathway, but not the NF-κB pathway (driven by TNFα), regulated CD209/CD14+ DC function in terms of activation, inflammatory state, and migratory capacity. In conclusion, we identified a novel CD209/CD14+ DC population, which is active in the circulation of RA and PsA, an effect potentiated once they enter the joint. Furthermore, we demonstrated that JAK/STAT inhibition can be used as a therapeutic strategy to decrease the inflammatory state of the pathogenic CD209/CD14+ DC.